Reciprocation wary employees discount psychological contract fulfillment. (19th May 2015) - Karagonlar, Gökhan; Eisenberger, Robert; Aselage, Justin
Summary: The present study examined the moderating role of reciprocation wariness in the association of employees' psychological contract fulfillment with psychosomatic strain and voluntary turnover, as mediated by perceived organizational support. To study these relationships longitudinally, 169 graduating college seniors were surveyed upon job acceptance and again 3 weeks, 3 months, 6 months, and 18 months following the start of employment. The findings showed that psychological contract fulfillment was positively related to perceived organizational support. However, this positive relationship was eliminated by reciprocation wariness, and this influence was carried over to psychosomatic strain and voluntary turnover. Thus, it appears that reciprocation wariness leads employees to discount psychological contract fulfillment as an indication of the organization's valuation and caring. Copyright © 2015 John Wiley & Sons, Ltd.